EXPERIMENTAL JUSTIFICATION OF NEW WAY OF PHARMACOLOGICAL CORRECTION FOR CONTACT FROSTBITE USING DSLET OPIOID PEPTIDE AND SEROTONIN ADIPINATE TO ENHANCE SURGYCAL TREATMENT - Alexander Chigunadze; Elena Artyushkova; Vladimir N.Mishustin; Galina Goryainova; Ekaterina Artyushkova (Belgorod National Research University, 2016)
The severity of complications and a large percentage of disability related to the occurrence cold injury lead to medical, social and economic problems. Considering the contact of cold injury as a variety of acute ischemia with the subsequent formation of early and late postischemic disorders as causes of disorders of blood circulation in the affected segments can be considered a disorder of the oxidant-antioxidant status and cytokine, systemic inflammation, reperfusion syndrome, the development of endothelial dysfunction, which ultimately leads to multiple organ failure. In the course of the study when assessing the microcirculatory changes caused by the simulation of frostbite, the most pronounced effect of the combined treatment of Serotonin adipinate 4.5 mg/kg and opioid peptide DSLET 10 μg/kg compared with monotherapy with the studied drugs was estimated. The most effective correction of indices of oxidantantioxidant protection observed with the combination of necrectomy with a combination of Serotonin adipinate and opioid peptide DSLET, which was confirmed by approximating the indicators of malondialdehyde, superoxide dismutase, finite stable metabolites of nitrogen oxide, total antioxidant activity and catalase to the values of intact animals on the 14th day of the experiment and reducing the level of proinflammatory cytokines (interleukin-6, tumor necrosis factor-alpha) in 2 times (p < 0.05) compared to the Control group. The combined use of Serotonin adipinate 4.5 mg/kg and opioid peptide DSLET of 10 μg/kg in combination with active surgical tactics (necrectomy) helps reduce the severity and prevalence of alternative changes, accelerate the formation of granulation shaft, a more intense development of reparative processes in the simulation of cold injury compared with the monotherapy. The combined use of investigational drugs in combination with active surgical tactics led to the maximum enhancement of the survival of the animals with contact frostbite in the experiment.